JENSEN TYPE WEIGHTED INEQUALITIES FOR FUNCTIONS OF SELFADJOINT AND UNITARY OPERATORS - Dragomir, S.S. (Italian Journal of Pure and Applied Mathematics, 2014)
On making use of the spectral representations in terms of the Riemann-Stieltjes integral for the selfadjoint and unitary operators in Hilbert spaces we establish here some weighted inequalities of Jensen’s type for convex, square-convex and Arg-square-convex functions. Some applications for simple functions of operators that belong to those classes are also provided.